1388Risk factors for chronic cough in adults: A systematic review and meta-analysis. (2nd September 2021) - Zhang, Jingwen; Perret, Jennifer; Chang, Anne; Idrose, Nur; Bui, Dinh; Lowe, Adrian; Abramson, Michael; Haydn Walters, E.; Lodge, Caroline; Dharmage, Shyamali
Abstract: Background: Despite the challenges of diagnosing and managing adult patients with chronic cough, a systematic synthesis of evidence on aetiological risk factor is lacking. Methods: We systematically searched PUBMED and EMBASE to synthesize the current evidence for longitudinal associations between various risk factors and chronic cough in the general adult population, following the meta-analysis of observation studies in epidemiology (MOOSE) guidelines. The Newcastle-Ottawa scale was used to assess the quality of the included studies. Fixed-effect meta-analysis was conducted where appropriate. Results: Of 26 eligible articles, 16 domains of risk factors were assessed. There was consistent evidence that asthma (pooled adjusted OR (aOR) = 3.01; 95%CI: 2.33-3.70; I2=0%, number of articles (N)=3) and low education levels/socioeconomic status (SES) (pooled aOR=1.46; 95%CI: 1.20-1.72; I2=0%; N = 3) were associated with an increased risk of chronic cough after adjusting for smoking and other confounders. While continuous smoking was associated chronic cough (aOR =1.81; 95%CI: 1.36, 2.26; I2=57%; N = 3), there was too little evidence to draw conclusions for occupational exposures, outdoor air pollution, early-life exposures, diet, snoring and other chronic conditions. Conclusions: Asthma, persistent smoking and lower education/SES were associated with increased risk of chronic cough. Longitudinal associations between other factors frequently mentioned empirically need further investigation. Key messages: Our systematic review found asthma, smoking and lower education to be associated with adult chronic cough. More longitudinal studies are needed to understand other potential risk factors for adult chronic cough.